Parkinson's disease‐associated receptor GPR37 is an ER chaperone for LRP6 - Berger, Birgit Sandra; Acebron, Sergio P.; Herbst, Jessica; Koch, Stefan; Niehrs, Christof (EMBO reports, 2017)
Wnt/β‐catenin signaling plays a key role in embryonic development, stem cell biology, and neurogenesis. However, the mechanisms of Wnt signal transmission, notably how the receptors are regulated, remain incompletely understood. Here we describe that the Parkinson's disease‐associated receptor GPR37 functions in the maturation of the N‐terminal bulky β‐propellers of the Wnt co‐receptor LRP6. GPR37 is required for Wnt/β‐catenin signaling and protects LRP6 from ER‐associated degradation via CHIP (carboxyl terminus of Hsc70‐interacting protein) and the ATPase VCP. GPR37 is highly expressed in neural progenitor cells (NPCs) where it is required for Wnt‐dependent neurogenesis. We conclude that GPR37 is crucial for cellular protein quality control during Wnt signaling. Synopsis Using a genome‐wide siRNA screen, this study identifies the Parkinson's disease‐associated receptor GPR37 as a novel ER chaperone for the Wnt co‐receptor LRP6. In NPCs GPR37 functions to promote Wnt‐driven neurogenesis. GPR37 promotes the maturation of the N‐terminal domains E1‐2 of LRP6, thereby promoting Wnt signaling.GPR37 protects LRP6 from ER‐associated degradation (ERAD).In NPCs, GPR37 and LRP6 promote neuronal fate.